Bifidobacterium infantis Potentially Alleviates Shrimp Tropomyosin-Induced Allergy by Tolerogenic Dendritic Cell-Dependent Induction of Regulatory T Cells and Alterations in Gut Microbiota - Fu, Linglin; Song, Jinyu; Wang, Chong; Fu, Shujie; Wang, Yanbo (Frontiers in Immunology, 2017)
Shellfish is one of the major allergen sources worldwide, and tropomyosin (Tm) is the predominant allergic protein in shellfish. Probiotics has been appreciated for its beneficial effects on the host, including anti-allergic and anti-inflammatory effects, although the underlying mechanisms were not fully understood. In this study, oral administration of probiotic strain Bifidobacterium infantis 14.518 (Binf) effectively suppressed Tm-induced allergic response in a mouse model by both preventive and therapeutic strategies. Further results showed that Binf stimulated dendritic cells (DCs) maturation and CD103+ tolerogenic DCs accumulation in gut-associated lymphoid tissue (GALT), which subsequently induced Tregs differentiation for suppressing Th2-biased response. We also found that Binf regulates the alterations of gut microbiota composition. Specificly, the increase of Dorea and decrease of Ralstonia is highly correlated with Th2/Treg ratio and may contribute to alleviating Tm-induced allergic responses. Our findings provide molecular insight into the application of Binf in alleviating food allergy and even gut immune homeostasis.